THE PROBLEM OF INTEGRATION OF HIGHER MATHEMATICS WITH ECONOMIC CYCLE DISCIPLINES IN THE PROCESS OF TEACHING STUDENTS - Khomyuk, Victor; Bondarenko, Zlata; Kyrylashchyk, Svitlana; Chernovolyk, Galyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the article is to show the necessity of developing the ability of conscious use of the fundamental discipline “Higher Mathematics” potential for a holistic solution of professional economic problems for students of economic specialities. This is only possible through interdisciplinary integration. It is shown that mathematics is a number of disciplines that are sometimes intersected, and sometimes significantly differ from each other in objects and research methods. As practice shows, quite often students’ knowledge in mathematics remains formal, and skills are unformed.For creation an integrative model of basic mathematical and economic disciplines, the article carries out two structural and logical analyses of the academic disciplines’ content: internal and external. The internal means a structural-logical analysis of the topics content of higher mathematics for identifying their leading positions and the main interconnecting elements within a given discipline. The external means a structural-logical analysis of the topics content of other disciplines specialty curriculum in order to determine the degree of their content overlap with the content of mathematical topics and the identification of “supporting” interdisciplinary knowledge that must be used for scientific and comprehensive reveal of the leading positions of higher mathematics.